Antibiotic-Impregnated Cement Embedding Technique for Spinal Instrumentation Infections - Kato, So; Hozumi, Takahiro; Yamakawa, Kiyofumi; Goto, Takahiro; Kondo, Taiji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background and Study Aims When surgical site infection occurs in patients with an instrumented spine, the management of infection is challenging because a biofilm is formed around the metallic surface of the implant. Although a wide variety of methods to salvage implants has been developed, previously reported methods reduce the patients' quality of life and are frequently time consuming and costly.Patients and Methods We performed a cement embedding technique in 13 consecutive patients with infection after spinal instrumentation. After meticulous open débridement, the metallic implants were embedded using polymethylmethacrylate (PMMA) mixed with antibiotics. Antibiotics were selected in each case according to the pathogens and their sensitivity. The wound was primarily closed. We did not restrict the patients' activity postoperatively. The implants were not removed unless it was necessary for further procedures.Results Nine patients, including those infected by methicillin-resistant Staphylococcus aureus (MRSA), were cured by débridement and PMMA embedding followed by systemic antibiotic treatment. No complications were reported.Conclusions The antibiotic-impregnated PMMA embedding technique is an effective method for the treatment of spinal instrumentation infections. It is easy to perform and is also effective for MRSA infection.
Keywords: spinal instrument; infection; antibiotic impregnated cement; embedding